A simple method for assessing intestinal inflammation in Crohn's disease. Issue 4 (1st October 2000) - Tibble, J; Teahon, K; Thjodleifsson, B; Roseth, A; Sigthorsson, G; Bridger, S; Foster, R; Sherwood, R; Fagerhol, M; Bjarnason, I
Abstract : BACKGROUND AND AIMS: Assessing the presence and degree of intestinal inflammation objectively, simply, and reliably is a significant problem in gastroenterology. We assessed faecal excretion of calprotectin, a stable neutrophil specific marker, as an index of intestinal inflammation and its potential use as a screening test to discriminate between patients with Crohn's disease and those with irritable bowel syndrome. METHODS: The validity of faecal calprotectin as a marker of intestinal inflammation was assessed in 22 patients with Crohn's disease (35 studies) by comparing faecal excretions and concentrations using four day faecal excretion of 111 indium white cells. A cross sectional study assessed the sensitivity of faecal calprotectin concentration for the detection of established Crohn's disease (n=116). A prospective study assessed the value of faecal calprotectin in discriminating between patients with Crohn's disease and irritable bowel syndrome in 220 patients referred to a gastroenterology clinic. RESULTS: Four day faecal excretion of 111 indium (median 8.7%; 95% confidence interval (CI) 7–17%; normal <1.0%) correlated significantly (p<0.0001) with daily (median ranged from 39 to 47 mg; normal <3 mg; r =0.76–0.82) and four day faecal calprotectin excretion (median 101 mg; 95% CI 45–168 mg; normal <11 mg; r =0.80) and single stool calprotectin concentrations (median 118 mg/l; 95% CI 36–175 mg/l; normal <10 mg/l; r =0.70) in patients with Crohn's disease. The cross sectional study showed a sensitivity of 96% for calprotectin in discriminating between normal subjects (2 mg/l; 95% CI 2–3 mg/l) and those with Crohn's disease (91 mg/l; 95% CI 59–105 mg/l). With a cut off point of 30 mg/l faecal calprotectin has 100% sensitivity and 97% specificity in discriminating between active Crohn's disease and irritable bowel syndrome. CONCLUSION: The calprotectin method may be a useful adjuvant for discriminating between patients with Crohn's disease and irritable bowel syndrome.